Global energy: need, present status, future trend and key issues - Uddin, Md. Nasir; Rashid, Muhammad Mahbubur; Mostafa, Mohammad Golam; Hossain, Belayet; Nithe, N. A. (Global Journals Inc. (USA), 2016)
Human beings, unlike other biological species, had always and still have the universal desire or instinct of improving quality of life. This inherent instinct has caused previously unimagined explosion of amenities of life, change in life style, improvement of standard of living and resulted sharp growth of global population and life expectancy. Better quality of life requires more works to be done to cook food, build housing, construct roads, and produce clothes and lighting and primarily to generate motive power to produce present day goods and services. Energy sources are needed to fulfill the ever-increasing human needs. Traditional sources of energy e.g. firewood and vegetable wastes, animal power, wind, sun and the traditional ways of using these sources could not match with the increased energy demand. Commercial energy sources: coal, oil and gas are presently playing the dominant role. But the reserves of these sources are finite. New and renewable energy sources like: hydro, nuclear, solar, wind, hydrogen, synthetic oils etc. are also contributing to meet the rising global energy demand but the contribution of these sources is still very limited..